Psychological and Physiological Effects of the Mindful Lovingkindness Compassion Program on Highly Self-Critical University Students in South Korea - Noh, Seunghye; Cho, Hyunju (Frontiers in Psychology, 2020)
Objectives Self-critical behavior is especially relevant for university students who face academic and non-academic stressors, leading to negative outcomes such as mental distress and psychopathologies. To address this behavior, mindfulness and compassion are important factors to decrease self-criticism and ensure positive outcomes. This study examined the psychological and physiological effects of an intervention, the Mindful Lovingkindness Compassion Program (MLCP), on highly self-critical university students in South Korea. Methods Thirty-eight university students with a high level of self-criticism were assigned to an MLCP group (n = 18) or waitlist (WL) group (n = 20). Self-report measures of self-criticism, self-reassurance, psychological distress, and other mental health variables were completed, and the physiological measure of heart rate variability (HRV) was conducted before and after the intervention with both groups. In addition, 1- and 3-month follow-up assessments were conducted using self-report measurements. Results Compared to the WL group, participants in the MLCP group experienced significantly greater reductions in self-criticism and psychological distress, and a greater increase in self-reassurance, mental health, and HRV. The improvements in the self-report measures were maintained when assessed 1 and 3 months later. Conclusions MLCP could be a promising intervention for alleviating self-criticism and increasing self-reassurance among self-critical individuals.